TEACHER REPRESENTATIVE AS DEMONSSTRATOR; ACTUALIZATION OF FIGURES FOR STUDENTS - Zubaidi, Ahmad; Hamada, Samir; Harozim, Abdul Hannan (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
The essence of the problem of current learning patterns is that there is still a delay in students' understanding of the material as a whole. So the purpose of this study is to find out how the teacher's representation as a demonstrator who actualizes himself becomes a figure for students. This study uses a qualitative approach to the type of phenomenology at the Islamic Elementary School Terpadu Permata Kraksaan. The data collection technique was through observation, in-depth interviews with the school principal, Vice Head of Student Affairs, Deputy Head of Curriculum, homeroom teachers for class I, and II, as well as related documentation. The data analysis technique uses the Miles and Huberman Interactive Model by reducing data, presenting data, and drawing conclusions. The validity of the data is reached by the process of triangulation of sources and techniques. The results of the study show that SDIT Permata Kraksaan requires its teachers to be practitioners of good demonstrators for students. Teacher representatives as demonstrators are actualized with personal capability, capability to innovate, and capability to develop. The role of teachers with various skills makes it easier for students to understand simply and clearly. The learning process will also be dynamic and rich in broad insights. Of course, this research will be a scientific charity for educational practitioners in positioning themselves for educational success. More importantly, the utility of the teacher figure as a demonstrator will make it easier for students to reach wider information.